Preparation method of high-purity phenolic resin carbon microspheres

By using chelating resin for raw material purification and the use of non-metallic catalysts, combined with the equipment's non-metal treatment, the problem of difficult removal of magnetic substance impurities in phenolic resin carbon materials is solved, and the preparation of high-purity phenolic resin carbon microspheres is achieved, which improves the cycle life and safety of the battery.

CN119898753AActive Publication Date: 2025-04-29SHANDONG SENJIU BIOMATERIALS CO LTD

Patent Information

Application Number
CN202510081641.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove magnetic substance impurities in phenolic resin carbon materials, such as iron, cobalt, chromium, nickel and zinc, which affects the cycle life, safety and stability of the battery.

Method used

The raw materials were purified by amine carboxylic acid or amine phosphoric acid chelating resin, combined with non-metallic catalysts and equipment non-metal treatment methods to prepare high-purity phenolic resin carbon microspheres.

Benefits of technology

It significantly reduces the impurity content in carbon microspheres, improves the purity and conductivity of the material, and enhances the safety and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898753A_ABST
    Figure CN119898753A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of high-purity phenolic resin carbon microspheres, and belongs to the technical field of battery materials, the preparation method mainly comprises the steps of purification, polymerization, separation, drying and carbonization of raw materials, the resin carbon microspheres obtained through the method are large in density, high in purity and good in strength, the ash content is smaller than 0.01%, the total content of microelements (iron, cobalt, chromium, nickel and zinc) is smaller than 100 ppb, and the service life of the resin carbon microspheres is prolonged. The material can be used as a precursor of negative electrode materials of silicon carbon, phosphorus carbon and hard carbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and specifically relates to a method for preparing high-purity phenolic resin carbon microspheres. Background Art

[0002] Carbon materials are widely used as negative electrode materials for batteries, such as graphite and hard carbon. Phenolic resin carbon is increasingly used in high-end carbon materials due to its high carbon content, thermal stability and low cost, especially its good microstructure adjustment function and subsequent activation and pore-forming function.

[0003] In recent years, negative electrode materials such as silicon carbon, phosphorus carbon and hard carbon are more widely used in high-end batteries and new batteries. These negative electrode materials require resin carbon to have good conductivity, good strength, good resistance to charge and discharge volume expansion stress and low impurities, especially lower magnetic material impurities (iron, cobalt, chromium, nickel, zinc). In patent CN116395665A, a homogeneous spherical carbon material manufacturing process is proposed, and the homogeneous spherical carbon material greatly improves the negative electrode material charge and discharge anti-expansion internal stress. Patent CN104387239B mentions the use of cation exchange resin to purify phenol to prepare nonyl phenol, but phenol is weakly acidic, and high concentration of phenol will affect the ion exchange balance, resulting in metal cation impurities in phenol being difficult to be exchanged or the exchange amount is extremely low. With the needs of high-end batteries, impurities in carbon materials, especially magnetic material impurities (iron, cobalt, chromium, nickel, zinc) elements, may cause electrochemical side reactions in batteries, affecting the cycle life, safety and stability of batteries. Summary of the invention

[0004] To solve the above problems, the purpose of the present invention is to provide a method for preparing high-purity phenolic resin carbon microspheres.

[0005] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0006] A method for preparing high-purity phenolic resin carbon microspheres, comprising purification, polymerization, separation, drying and carbonization of raw materials;

[0007] The purification of the raw material is carried out by using aminocarboxylic acid type chelating resin or aminophosphoric acid type chelating resin.

[0008] The method for preparing high-purity phenolic resin carbon microspheres specifically comprises the following steps:

[0009] 1) Purification of raw materials: Phenol is melted into liquid and passed through ion exchange column A; the aldehyde compound solution passes through ion exchange column B to obtain purified phenol and aldehyde compounds;

[0010] 2) Polymerization: the purified phenol and aldehyde compound, non-metallic ion catalyst and solvent prepared in step 1) are sequentially added into a reaction kettle, and prepolymerized at 50-80° C. for 0.1-5 h under stirring, and then a dispersant is added thereto to form spherical droplets, and then the temperature is continuously raised to 80-150° C., and a curing reaction is performed for 0.5-10 h, and then cooled to obtain a phenolic resin suspension;

[0011] 3) separation: filtering the phenolic resin suspension obtained in step 2) through a filter to obtain solid phenolic resin and mother liquor;

[0012] 4) Drying: Drying the solid phenolic resin obtained in step 3) to obtain a thermosetting phenolic resin;

[0013] 5) Carbonization: The thermosetting phenolic resin obtained in step 4) is placed in a high temperature furnace, carbonized at 500-900° C. for 0.5-10 h, cooled, discharged, and broken up to obtain high-purity phenolic resin carbon microspheres.

[0014] In step 1), the ion exchange column A is filled with one or both of aminocarboxylic acid type chelating resin and aminophosphoric acid type chelating resin and has a heat-insulating interlayer; the ion exchange column B is filled with one or both of aminocarboxylic acid type chelating resin and aminophosphoric acid type chelating resin and does not require a heat-insulating interlayer.

[0015] The aldehyde compound in step 1) is one or two of formaldehyde, acetaldehyde and paraformaldehyde.

[0016] The non-metallic ion catalyst in step 2) is one or two of aniline, urotropine, ammonia water, triethylamine, trimethylamine, diethanolamine, triethanolamine and diammonium hydrogen phosphate.

[0017] The solvent in step 2) is one or two of deionized water, propylene glycol, ethylene glycol, glycerin, turbine oil, vegetable oil and dioctyl phthalate.

[0018] The dispersant in step 2) is one or two of gelatin, gum arabic, polyvinyl alcohol, polyvinyl pyrrolidone, hydroxymethyl cellulose, carboxyethyl cellulose, methyl hydroxyethyl cellulose, lignin, polydimethyldiallylammonium chloride and sodium oleate.

[0019] The mass ratio of the phenol, the aldehyde compound, the non-metallic ion catalyst, the solvent and the dispersant in step 2) is 94:30-200:1-30:50-300:1-10.

[0020] The filter in step 3) is one or two of a high-speed centrifuge, a plate and frame filter press and a sedimentation tank.

[0021] The high temperature furnace in step 5) is one or two of a roller kiln, a tunnel kiln, a box furnace or a coating furnace.

[0022] The particle size of the high-purity phenolic resin carbon microspheres in step 5) is 2 to 1000 um.

[0023] The present invention also includes the use of high-purity phenolic resin carbon microspheres as precursors of negative electrode materials of silicon carbon, phosphorus carbon and hard carbon.

[0024] The parts of the equipment used in the preparation process of the present invention that are in contact with the materials need to be treated with non-metal, including but not limited to the following treatment methods: the ion exchange column is lined with glass fiber reinforced plastics, PP columns, carbon steel or stainless steel columns; the reaction kettle and pipeline are lined with polytetrafluoroethylene; the carburized crucible is made of silicon carbide or graphite crucible, and the pulverizer is lined with ceramic.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] The present invention invents for the first time a kind of industrially practicable high-purity phenolic resin carbon microspheres, and the high-purity phenolic resin carbon microspheres are prepared by purifying, polymerizing, separating, drying and carbonizing raw materials. First, the purity of the raw materials is controlled. Industrial-grade phenol and formaldehyde, which are upstream raw materials of phenolic resin carbon, are usually acidic and corrosive to commonly used stainless steel or galvanized production equipment, pipelines or storage tanks, thereby bringing in some magnetic impurities, such as iron, cobalt, chromium, nickel and zinc elements. The present invention proposes for the first time to use chelating resin to purify the raw material phenol or aldehyde compound. The functional groups in the chelating resin can complex with impurity ions in a weak acid system and selectively adsorb impurity metal ions, thereby reducing an important source of impurities in carbon microspheres; secondly, non-metallic catalysts are selected. Inorganic acid or alkaline catalysts are commonly used in phenolic condensation. Conventional catalysts will cause inorganic ions to remain in the resin and cannot be volatilized in the subsequent carbonization, thereby affecting the purity of the carbon material; thirdly, non-metallic treatment of production equipment, the equipment parts that contact the production materials, the low-temperature part is lined with rubber or polytetrafluoroethylene, and the high-temperature equipment is lined with ceramic or silicon carbide or graphite.

[0027] The invention realizes high-purity control of carbon microsphere products by purifying raw materials, and non-metallizing treatment of pure organic raw and auxiliary materials and manufacturing equipment. The high-purity phenolic resin carbon microspheres prepared by the invention have a particle size between 2 and 1000 μm. The particle size is lower than 2 μm, and the subsequent processing performance is poor. Meanwhile, too small a particle size has a small compaction density and a large specific surface area, which affects the battery capacity and the first efficiency. The larger the particle size, the worse the internal heat transfer of the particles during preparation, which affects the uniformity of the microstructure. The volume resistivity is lower than 1 Ω·cm, the ash content is lower than 0.01%, the carbon content is greater than 99.99%, and the total content of impurity trace elements (iron, cobalt, chromium, nickel, zinc) is less than 100 ppb. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a particle size distribution diagram of high-purity phenolic resin carbon microspheres prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] In order to better understand the technical solution of the present invention, the above content of the present invention is further described in detail below through specific implementation methods in the form of embodiments, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above content of the present invention belong to the scope of the present invention.

[0030] Embodiment 1 Phenol is melted into liquid state and passed through a polytetrafluoroethylene-lined stainless steel ion exchange column filled with aminocarboxylic acid type chelating resin; a formaldehyde aqueous solution with a mass concentration of 37% is passed through a PP ion exchange column filled with aminophosphoric acid type chelating resin; purified phenol and formaldehyde aqueous solution are obtained; 94 g of purified phenol and 85 g of purified formaldehyde aqueous solution, 10 g of ammonia water with a mass concentration of 25% and 100 g of ethylene glycol are added to a reaction flask in sequence, and prepolymerized at 75°C under stirring. After reacting for 0.5h, 5g of sodium oleate was added to form spherical droplets, and then the temperature was continued to rise to 120°C, and the curing reaction was carried out for 7h, and then cooled to obtain a phenolic resin suspension; the obtained phenolic resin suspension was filtered through a high-speed centrifuge to obtain a solid phenolic resin and a mother liquor; the obtained solid phenolic resin was dried to obtain a thermosetting phenolic resin; the obtained thermosetting phenolic resin was placed in a roller kiln, carbonized at 600°C for 5h, cooled, discharged, and broken up to obtain high-purity phenolic resin carbon microspheres. Its particle size detection spectrum is as follows Figure 1 shown.

[0031] Embodiment 2 Phenol is melted into liquid state and passed through a polytetrafluoroethylene-lined stainless steel ion exchange column filled with aminocarboxylic acid type chelating resin; an acetaldehyde aqueous solution having a mass concentration of 40% is passed through a polytetrafluoroethylene-lined stainless steel ion exchange column filled with aminocarboxylic acid type chelating resin; purified phenol and acetaldehyde aqueous solution are obtained; 94 g of purified phenol and 75 g of purified acetaldehyde aqueous solution, 5 g of aniline and 150 g of glycerol are sequentially added into a reaction flask, and prepolymerization is carried out at 65° C. under stirring. 5h, then add 6g of gelatin to form spherical droplets, continue to heat to 110℃, cure reaction for 10h, cool to obtain phenolic resin suspension; filter the obtained phenolic resin suspension through a plate and frame filter press to obtain solid phenolic resin and mother liquor; dry the obtained solid phenolic resin to obtain thermosetting phenolic resin; put the obtained thermosetting phenolic resin into a tunnel kiln, carbonize at 500℃ for 10h, cool, discharge, and break up to obtain high-purity phenolic resin carbon microspheres.

[0032] Example 3 Phenol was melted into liquid state and passed through a polytetrafluoroethylene-lined stainless steel ion exchange column filled with an aminophosphoric acid type chelating resin; a paraformaldehyde solution was passed through a polytetrafluoroethylene-lined stainless steel ion exchange column filled with an aminophosphoric acid type chelating resin; purified phenol and paraformaldehyde solution were obtained; 94 g of purified phenol and 100 g of purified paraformaldehyde solution, 8 g of urotropine and 120 g of water were added to a reaction flask in sequence, and prepolymerization was carried out at 68° C. for 4 h under stirring, and then 4 g of hydroxymethyl cellulose is added thereto to form spherical droplets, and then the temperature is continued to be raised to 95°C, and the curing reaction is carried out for 8 hours, and the phenolic resin suspension is obtained; the obtained phenolic resin suspension is settled in a sedimentation tank, the upper mother liquor is discharged, and solid phenolic resin is obtained at the bottom; the obtained solid phenolic resin is dried to obtain a thermosetting phenolic resin; the obtained thermosetting phenolic resin is placed in a coating furnace, carbonized at 600°C for 7 hours, cooled, discharged, and broken up to obtain high-purity phenolic resin carbon microspheres.

[0033] Example 4 Phenol was melted into liquid state and passed through a PP ion exchange column filled with an aminophosphoric acid type chelating resin; a formaldehyde aqueous solution having a mass concentration of 37% was passed through a polytetrafluoroethylene lined stainless steel ion exchange column filled with an aminocarboxylic acid type chelating resin to obtain purified phenol and formaldehyde aqueous solution; 94 g of purified phenol and 150 g of purified formaldehyde aqueous solution, 15 g of triethanolamine and 150 g of turbine oil were sequentially added to a reaction flask, and the prepolymerization reaction was carried out at 70° C. for 3 hours under stirring. .5h, then add 5g of sodium oleate to form spherical droplets, continue to heat to 110℃, solidify for 7h, cool to obtain a phenolic resin suspension; filter the obtained phenolic resin suspension through a high-speed centrifuge to obtain a solid phenolic resin and a mother liquor; dry the obtained solid phenolic resin to obtain a thermosetting phenolic resin; put the obtained thermosetting phenolic resin into a box furnace, carbonize at 650℃ for 5h, cool, discharge, and break up to obtain high-purity phenolic resin carbon microspheres.

[0034] Example 5 Phenol was melted into a liquid state and passed through a PP ion exchange column filled with an aminophosphoric acid type chelating resin; an acetaldehyde aqueous solution having a mass concentration of 40% was passed through a polytetrafluoroethylene lined stainless steel ion exchange column filled with an aminophosphoric acid type chelating resin; purified phenol and acetaldehyde aqueous solution were obtained; 94 g of purified phenol and 120 g of purified acetaldehyde aqueous solution, 20 g of trimethylamine and 180 g of vegetable oil were added to a reaction flask in sequence, and the prepolymerization reaction was carried out at 75° C. for 2 hours under stirring. h, then add 6g of gum arabic thereto to form spherical droplets, continue to heat to 120°C, solidify for 6h, cool, and obtain a phenolic resin suspension; filter the obtained phenolic resin suspension through a high-speed centrifuge to obtain a solid phenolic resin and a mother liquor; dry the obtained solid phenolic resin to obtain a thermosetting phenolic resin; put the obtained thermosetting phenolic resin into a box furnace, carbonize at 700°C for 4h, cool, discharge, and break up to obtain high-purity phenolic resin carbon microspheres.

[0035] Example 6 Phenol was melted into a liquid state and passed through a PP ion exchange column filled with an aminophosphoric acid type chelating resin; an acetaldehyde aqueous solution having a mass concentration of 40% was passed through a polytetrafluoroethylene lined stainless steel ion exchange column filled with an aminocarboxylic acid type chelating resin; purified phenol and acetaldehyde aqueous solution were obtained; 94 g of purified phenol and 150 g of purified acetaldehyde aqueous solution, 12 g of aniline and 150 g of water were added to a reaction flask in sequence, and the prepolymerization reaction was carried out at 72° C. for 2.5 min under stirring. h, and then add 5g of lignin to it to form spherical droplets, continue to heat up to 98°C, cure reaction for 8h, cool, and obtain a phenolic resin suspension; filter the obtained phenolic resin suspension through a plate and frame filter press to obtain a solid phenolic resin and a mother liquor; dry the obtained solid phenolic resin to obtain a thermosetting phenolic resin; put the obtained thermosetting phenolic resin into a box furnace, carbonize at 750°C for 3h, cool, discharge, and break up to obtain high-purity phenolic resin carbon microspheres.

[0036] Embodiment 7 Phenol was melted into liquid state and flowed through a PP ion exchange column filled with an aminophosphoric acid type chelating resin; a formaldehyde aqueous solution having a mass concentration of 37% was flowed through a polytetrafluoroethylene lined stainless steel ion exchange column filled with an aminocarboxylic acid type chelating resin; purified phenol and formaldehyde aqueous solution were obtained; 94 g of purified phenol and 115 g of purified formaldehyde aqueous solution, 30 g of urotropine and 300 g of propylene glycol were added to a reaction flask in sequence, and the prepolymerization reaction was carried out at 80° C. under stirring. .5h, then add 7g of sodium oleate to form spherical droplets, continue to heat to 140°C, solidify for 3h, cool, and obtain a phenolic resin suspension; filter the obtained phenolic resin suspension through a plate and frame filter press to obtain a solid phenolic resin and a mother liquor; dry the obtained solid phenolic resin to obtain a thermosetting phenolic resin; put the obtained thermosetting phenolic resin into a box furnace, carbonize at 800°C for 2h, cool, discharge, and break up to obtain high-purity phenolic resin carbon microspheres.

[0037] Embodiment 8 Phenol is melted into liquid state and passed through a PP ion exchange column filled with an aminocarboxylic acid type chelating resin; a paraformaldehyde solution is passed through a polytetrafluoroethylene-lined stainless steel ion exchange column filled with an aminocarboxylic acid type chelating resin; purified phenol and paraformaldehyde solution are obtained; 94 g of purified phenol and 120 g of purified paraformaldehyde solution, 25 g of 25% ammonia solution, and 150 g of deionized water are added to a reaction flask in sequence, and the prepolymerization reaction is carried out under stirring at 74° C. 2h, then add 6g of sodium oleate to form spherical droplets, continue to heat to 120°C, cure reaction for 7h, cool to obtain a phenolic resin suspension; filter the obtained phenolic resin suspension through a plate and frame filter press to obtain a solid phenolic resin and a mother liquor; dry the obtained solid phenolic resin to obtain a thermosetting phenolic resin; put the obtained thermosetting phenolic resin into a box furnace, carbonize at 700°C for 4h, cool, discharge, and break up to obtain high-purity phenolic resin carbon microspheres.

[0038] Comparative Example

[0039] The preparation method of phenolic resin carbon microspheres is the same as that of Example 1, except that the raw materials phenol and formaldehyde aqueous solution are not purified by ion exchange column, and the parts of the equipment used in the preparation process that are in contact with the materials are not subjected to non-metal treatment.

[0040] The high-purity phenolic resin carbon microspheres prepared in Examples 1 to 8 and the phenolic resin carbon microspheres prepared in the comparative example were tested according to the method in the national standard GB / T24533-2019, wherein the analysis lines of Fe, Co, Gr, Ni and Zn were 238.204 nm, 228.616 nm, 267.716 nm, 231.604 nm and 213.857 nm, respectively. The test results are shown in Table 1.

[0041] Table 1 Performance test table of phenolic resin carbon microspheres prepared in Examples and Comparative Examples

[0042]

[0043] It can be seen from the results in Table 1 that the high-purity phenolic resin carbon microspheres prepared by the method of the present invention have a particle size between 2 and 1000 um compared with the comparative example; the volume resistivity is lower than 1 Ω·cm, and the conductivity is good; the ash content is significantly reduced, lower than 0.01%; the carbon content is higher than the comparative example, greater than 99.99%, and the total content of trace elements (iron, cobalt, chromium, nickel, zinc) is significantly lower than the comparative example, less than 100 ppb, with high purity and low impurities.

[0044] Although the above describes the specific implementation methods of the present invention, it does not limit the scope of protection of the present invention. Based on the technical solution of the present invention, various modifications or variations that can be made by those skilled in the art without creative work are still within the scope of protection of the present invention.

Claims

1. A method for preparing high-purity phenolic resin carbon microspheres, characterized in that: Including purification, polymerization, separation, drying and carbonization of raw materials; The purification of the raw material is carried out by using aminocarboxylic acid type chelating resin or aminophosphoric acid type chelating resin.

2. The method for preparing high-purity phenolic resin carbon microspheres according to claim 1, characterized in that: The specific steps include: 1) Purification of raw materials: Phenol is melted into liquid and passed through ion exchange column A; The aldehyde compound solution flows through the ion exchange column B to obtain purified phenol and aldehyde compounds; 2) Polymerization: the purified phenol and aldehyde compound, non-metallic ion catalyst and solvent prepared in step 1) are sequentially added into a reaction kettle, and prepolymerized at 50-80° C. for 0.1-5 h under stirring, and then a dispersant is added thereto to form spherical droplets, and then the temperature is continuously raised to 80-150° C., and a curing reaction is performed for 0.5-10 h, and then cooled to obtain a phenolic resin suspension; 3) separation: filtering the phenolic resin suspension obtained in step 2) through a filter to obtain solid phenolic resin and mother liquor; 4) Drying: Drying the solid phenolic resin obtained in step 3) to obtain a thermosetting phenolic resin; 5) Carbonization: The thermosetting phenolic resin obtained in step 4) is placed in a high temperature furnace, carbonized at 500-900° C. for 0.5-10 h, cooled, discharged, and broken up to obtain high-purity phenolic resin carbon microspheres.

3. The method for preparing high-purity phenolic resin carbon microspheres according to claim 2, characterized in that: In step 1), the ion exchange column A is filled with one or both of aminocarboxylic acid type chelating resin and aminophosphoric acid type chelating resin and has a heat-insulating interlayer; the ion exchange column B is filled with one or both of aminocarboxylic acid type chelating resin and aminophosphoric acid type chelating resin and does not require a heat-insulating interlayer.

4. The method for preparing high-purity phenolic resin carbon microspheres according to claim 2, characterized in that: The aldehyde compound in step 1) is one or two of formaldehyde, acetaldehyde and paraformaldehyde.

5. The method for preparing high-purity phenolic resin carbon microspheres according to claim 2, characterized in that: The non-metallic ion catalyst in step 2) is one or two of aniline, urotropine, ammonia, triethylamine, trimethylamine, diethanolamine, triethanolamine and diammonium hydrogen phosphate; the solvent in step 2) is one or two of deionized water, propylene glycol, ethylene glycol, glycerol, turbine oil, vegetable oil and dioctyl phthalate; the dispersant in step 2) is one or two of gelatin, gum arabic, polyvinyl alcohol, polyvinyl pyrrolidone, hydroxymethyl cellulose, carboxyethyl cellulose, methyl hydroxyethyl cellulose, lignin, polydimethyldiallylammonium chloride and sodium oleate.

6. The method for preparing high-purity phenolic resin carbon microspheres according to claim 2, characterized in that: The mass ratio of the phenol, the aldehyde compound, the non-metallic ion catalyst, the solvent and the dispersant in step 2) is 94:30-200:1-30:50-300:1-10.

7. The method for preparing high-purity phenolic resin carbon microspheres according to claim 2, characterized in that: The filter in step 3) is one or two of a high-speed centrifuge, a plate and frame filter press and a sedimentation tank.

8. The method for preparing high-purity phenolic resin carbon microspheres according to claim 2, characterized in that: The high-temperature furnace in step 5) is one or two of a roller kiln, a tunnel kiln, a box furnace or a coating furnace; the particle size of the high-purity phenolic resin carbon microspheres in step 5) is 2 to 1000 um.

9. The method for preparing high-purity phenolic resin carbon microspheres according to claim 2, characterized in that: The parts of the equipment used in the preparation process that come into contact with the materials need to be treated with non-metallic materials, including but not limited to the following treatment methods: ion exchange columns are lined with fiberglass, PP, carbon steel or stainless steel columns; reaction kettles and pipelines are lined with polytetrafluoroethylene; carburized crucibles are made of silicon carbide or graphite crucibles, and the pulverizer is lined with ceramic.

10. Use of the high-purity phenolic resin carbon microspheres according to claim 1 as precursors of negative electrode materials of silicon carbon, phosphorus carbon and hard carbon.

Citation Information

Patent Citations

  • A kind of method that improves p-nonylphenol content in nonylphenol product

    CN104387239B

  • Preparation method of homogeneous spherical hard carbon negative electrode material

    CN116395665A

  • Phenolic resin-based hard carbon microspheres, preparation method thereof, negative electrode material and secondary battery

    CN105914371A

  • Method for preparing thermosetting phenolic resin

    CN1175597A

  • Spherical active carbon and method for production thereof

    JP2011083758A

Cited By

  • Phenolic resin sphere-based hard carbon sodium-ion battery negative electrode material, negative electrode and preparation method and application thereof

    CN122853356A